Water-extractable organic matter and enzyme activity in three forest soils of the Mediterranean area (European Journal of Soil Biology, 2014)
Soil enzyme activities mediate key ecosystem functions of degradation, transformation and carbon mineralization. The study of microbial activity and its relations with water-extractable organic matter (WEOM) can be crucial to understand the dynamics of soil organic carbon pool. We investigated FDA-hydrolytic, β-glucosidase, cellulase, o-diphenol oxidase activities in soils under Fagus sylvatica (beech), Quercus ilex (holm-oak) and Quercus cerris (turkey-oak) stands. We investigated WEOM by liquid-state nuclear magnetic resonance (NMR) spectroscopy, useful to highlight the major functionalities in this fraction of soil organic matter. The highest enzyme activities, on mass basis, were recorded in soil under beech, with the highest organic carbon content. Reporting enzyme activities on organic carbon basis, it was possible to reveal enzyme enrichment for β-glucosidase and diphenol oxidase activities in soil under turkey-oak, with low organic matter. The 1H NMR spectra of WEOM highlighted a great richness of soluble organic compounds in soils with high organic carbon content, such as beech and holm-oak soils. All spectra are dominated by carbohydrate resonances. Spectra of WEOM from each stand exhibited specific signals. In WEOM from holm-oak, signals from substituted aliphatics account for up 28% of the total spectrum; in this sample signals from acetic and formic acids predominate, likely relating to the lower microbial utilization, according to the low heterotrophic (FDA-hydrolytic) activity. Only in WEOM from beech, signals from aromatics were detected probably related to the lower lignin degradation in soil, as expressed by the low phenol oxidase activity. However, the relationships among WEOM quality, tree species and microbial activity need further investigations.